Entre Linhas e Agulhas:: aprendizado e tradição na costura. - Pereira, Gyovanna Neri (2024)
This experience report seeks to provide an analysis of the trajectory and experiences of a seamstress whose entrepreneurial journey in the art of sewing reflects the importance of family tradition, resilience and adaptation. Coming from a lineage of women skilled in sewing, our informant/deponent absorbed the secrets of this craft since her childhood, transmitted empirically from one generation to another within her family. Her entrepreneurial journey began as a response to financial needs, leading her to transform her talent into her main source of income. Despite the financial and intermediary challenges on his journey, his determination led him to invest in his own studio, where he gained recognition and customer loyalty. The report also highlights adaptations to new demand patterns, especially during a pandemic, reflecting a growing awareness of sustainability and responsible consumption. However, our informant's story also highlights the challenges faced, including the risk to their health due to overwork, highlighting the importance of setting limits and prioritizing personal well-being.